2019
DOI: 10.3390/j2040028
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in Children and Young Adults (Offspring) Born after Medically Assisted Reproduction: A Systematic Review and Meta-Analysis

Abstract: Many studies have investigated the relationship between medically assisted reproduction (MAR) and health outcomes, particularly cancer, in the offspring. This meta-analysis investigated the association between MAR and childhood cancer. Data sources were PubMed, Scopus, and Web of Science up until June 2018. From the selected studies, we extracted the cancer risk estimates of the exposure of interest (MAR, assisted reproductive technology—ART, and in fitro fertilization—IVF). We conducted the meta-analysis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Studies on risk of childhood cancer after ART show conflicting results. Most large observational studies indicate similar overall cancer risk in children born after ART and in children in the general population [20][21][22][23], but a higher risk for both any cancer [24][25][26][27] and specific malignancies [20,21,[24][25][26] has also been reported. In a Danish populationbased registry study [22], a higher risk of any childhood cancer was found after FET compared to spontaneous conception, but the finding was based on a limited number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on risk of childhood cancer after ART show conflicting results. Most large observational studies indicate similar overall cancer risk in children born after ART and in children in the general population [20][21][22][23], but a higher risk for both any cancer [24][25][26][27] and specific malignancies [20,21,[24][25][26] has also been reported. In a Danish populationbased registry study [22], a higher risk of any childhood cancer was found after FET compared to spontaneous conception, but the finding was based on a limited number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…If the in utero transfer of a pre-leukemic clone was the main causal pathway underlying the increased leukemia risk of twins, the risk among twins in this analysis should resemble that of singletons. Another possible explanation might be an adverse event of medical interventions associated with multiple birth such as fertility treatments, medically assisted reproduction (MAR) [53,55], and prelabour cesarean delivery [52]. In the FSO birth records, the proportion of multiple births among total births increased almost linearly with maternal age, from 1.6% among mothers aged 25 years or younger to 4.2% among those aged 40 years and above.…”
Section: Discussionmentioning
confidence: 99%
“…More than a century has passed since the pioneering work of Wesley Kingston Whitten (1956), the father of embryo culture medium [36], and signi cant progress has been made in culturing human and, to some extent, domestic species zygotes to blastocysts and then to embryos [37]. However, recent studies on humans have shown that culture media composition and assisted reproductive technology (ART) procedures affect parturition [38], the weight of children at birth, and even their health after ART procedure [39]. Despite these achievements in culturing human embryos, there is a need for further research, especially in culturing embryos from domestic species towards complete epigenetic patterns.…”
Section: Discussionmentioning
confidence: 99%